Determinan Psikologis Ibu Rumah Tangga dengan HIV (+) di Provinsi Kalimantan Tengah - Nurhalina Nurhalina; Nurul Chusna; Srie Rosmilawati (Borneo Journal of Medical Laboratory Technology, 2018)
Housewives living with HIV AIDS are a new trend in the HIV epidemic in Indonesia. Overall heterosexual transmission is the primary mode of transmission that dominates new case findings (69.6%) in 2017. Cumulative frequency of HIV/AIDS is 810 cases in Central Kalimantan. Housewives (19.4%) were the highest group after the private group. The purpose of this study was to look at the psychological determinants of housewives living with HIV (+) in Central Kalimantan Province. The method of this study was an observational analytic cross-sectional study. The population is patients who visit RSUD dr. Sylvanus Palangka Raya, RSUD dr. Murjani Sampit, Sultan Immanudin Pangkalanbun Hospital, and RSUD Dr.H Soemarno S Kuala Kapuas. Samples are excluded if there are psychiatric disorders and death sickness. The results showed that sociodemographic variables such as age, marriage history, ethnicity, education level, employment status, number of children, length of diagnosis and phase of HIV were not the psychological determinants of the respondents (p> 0.05).